Regio- and Stereoselective Synthesis of 2′-Deoxy-4′-thioguanine Nucleosides: Evaluation of Anti-Hepatitis B Virus Activity and Cytotoxicity Leading to Improved Selectivity Index by 4′-C-Cyanation - Kumamoto, Hiroki; Imoto, Shuhei; Kuwata-Higashi, Nobuyo; Mitsuya, Hiroaki; Haraguchi, Kazuhiro (Synlett, 2023)
An N9-regio- and β-anomer-selective 4′-thioglycosidation of purine bases has been developed. The reaction between a 2-deoxy-2-iodo-4-thioribofuranosyl glycosyl donor and N-(6-chloro-9H-purin-2-yl)-2-methylpropanamide gave the corresponding 2′-deoxy-4′-thiopurine nucleoside in 87% yield along with its N7-regioisomer in 6% yield, without the formation of the α-anomer. By using a derivative obtained from 17, a practical chemical synthesis of 2′-deoxy-4′-thioguanosine was developed. 4′-α-C-Cyano-2′-deoxy-4′-thioguanosine was synthesized, starting from a 4-(acetoxymethyl)-2-deoxy-2-iodo-4-thioribofuranose derivative as a glycosyl donor. An evaluation of the anti-hepatitis B virus (HBV) activity and the cytotoxicity toward the host cell revealed that 4'-C-cyano-2'-deoxy-4'-thioguanosine exhibited about 100 times more potent anti-HBV activity than 2′-deoxy-4′-thioguanosine with a comparative cytotoxicity, resulting in the identification of a novel molecule having better selectivity index value than that of 2′-deoxy-4′-thioguanosine. This finding might provide a guideline for the development of the next generation of anti-HBV agents.
Keywords: nucleosides; glycals; deoxythioguanosine; medicinal chemistry; cytotoxicity; hepatitis B virus